Physical Activity and the Gut Microbiota: Mechanisms and Clinical Relevance - literature review - Pracoń, Karolina; Pietrzak, Maria; Chawryło , Aneta; Łupina-Romaniuk , Marcela; Piecuch , Dominika; Oleksińska , Karolina; Świetlicka, Gabriela; Pietraś , Paulina; Stolarczyk , Michał; Kołodziejczyk , Julia (Quality in Sport, 2026)
Background: The gut microbiota is an integral component of human homeostasis, participating in the regulation of metabolic, immunological, and neuroendocrine processes. Alterations in its composition and function have been associated with the development of numerous chronic diseases, thereby increasing interest in lifestyle factors that can modulate the intestinal microbial ecosystem. Among these factors, physical activity has emerged as a potentially important determinant of gut microbiota composition and function. Aim: This narrative review aimed to evaluate current evidence regarding the effects of physical activity on the composition and function of the gut microbiota, with particular emphasis on underlying biological mechanisms, clinical relevance, and the limitations of the available scientific evidence. Materials and Methods: A literature search was conducted using the PubMed database. Observational, interventional, experimental, and review studies investigating the relationship between physical activity and the gut microbiota were included. Results: Current evidence suggests that regular moderate physical activity may promote beneficial alterations in the gut microbiota, including increased microbial diversity, enhanced abundance of short-chain fatty acid (SCFA)-producing bacteria, and improved intestinal barrier integrity. In contrast, prolonged and intensive exercise may contribute to transient gastrointestinal disturbances, increased intestinal permeability, and enhanced inflammatory responses. Interpretation of the available findings is complicated by the substantial influence of confounding factors, particularly diet, pharmacotherapy, body composition, and training status.